Electro-deposition and re-oxidation of carbon in carbonate containing molten salts - Happiness V. Ijije; Richard C. Lawrence; Nancy Julius Siambun; Sang, Mun Jeong; Daniel A. Jewell; Di, Hu; Chen, George Zheng (Royal Society of Chemistry, 2014)
The electrochemical deposition and re-oxidation of solid carbon were studied in CO3(2-) ion-containing molten salts (e.g. CaCl2-CaCO3-LiCl-KCl and Li2CO3-K2CO3) at temperatures between 500 and 800 °C under Ar, CO2 or N2-CO2 atmospheres. The electrode reactions were investigated by thermodynamic analysis, cyclic voltammetry and chronopotentiometry in a three-electrode cell under various conditions. The findings suggest that the electro-reduction of CO3(2-) is dominated by carbon deposition on all three tested working electrodes (Ni, Pt and mild steel), but partial reduction to CO can also occur. Electro-re-oxidation of the deposited carbon in the same molten salts was investigated for potential applications in, for example, direct carbon fuel cells. A brief energy and cost analysis is given based on results from constant voltage electrolysis in a two-electrode cell.